A Tracer Study on Employment Outcomes and Career Progression of Bachelor of Science in Information Technology (BSIT) Graduates: Basis for Enhancing Institutional Reputation and Graduate Employability - Demafeliz, Reynan E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This tracer study investigates the employment outcomes and career progression of Bachelor of Science in Information Technology (BSIT) graduates from Sultan Kudarat State University (SKSU) - Kalamansig Campus from 2018 to 2022. The research focuses on several key aspects: sociodemographic and academic profiles, employment status, the relevance of the BSIT degree to current occupations, the competencies developed during the program, and the challenges graduates face in the job market. Utilizing a quantitative descriptive approach, the study surveyed 159 out of 179 graduates and provided an assessment of their transition from enrolment to employment. Findings reveal that most graduates are employed, with a significant number working locally; however, many hold contractual or temporary positions. The BSIT degree generally proves relevant to their current jobs, particularly in technical fields. However, disparities in income and employment stability are evident. Key competencies, such as technical, critical thinking, and problem-solving skills, were well-developed; however, gaps in soft skills, leadership, and entrepreneurial capabilities were identified. Graduates also reported challenges, including a lack of Civil Service eligibility, limited job opportunities, and the absence of advanced degrees. The study emphasizes the need for curriculum enhancements that incorporate the development of soft skills and leadership training. It recommends stronger career counseling services and closer university-industry partnerships to ensure alignment between academic outputs and labor market demands. Additionally, the study advocates for institutional support in helping graduates pursue advanced degrees and gain eligibility for the Civil Service to improve their employment prospects. These interventions are crucial not only to enhance individual career outcomes but also to strengthen the university's reputation and its contribution to the national workforce.